Diagnostic Value of Diffusion-weighted Magnetic Resonance (MR) Imaging and MRS in Assessment of Malignant Brain Lesions - Sammer Saeed, Saima Ameer, Haroon Saeed, Uzma Habib, Nadia Hanif, Smeera Siddique (Pakistan Journal of Medical & Health Sciences, 2022)
Background: The purpose of the study is to evaluate the diagnostic value of DWI and MRS in assessment of the malignant brain lesions. Materials and methods: The study was conducted in Department of Diagnostic Radiology from March 2021, to December 2021 in Lahore General Hospital. Sample size selected was 50 patients referred to the Department of Diagnostic Radiology for their suspected brain lesion assessments. The patients were evaluated by the DWI magnetic resonance imaging and MRS. Classifications of lesions were benign and malignant on the basis of radiological findings. The data was compared with the histopathological results as a gold standard. Results: The malignant lesions from benign lesions were differentiated with DWI images and ADC mapping. Lower ADC values with restricted diffusion was considered malignant and higher ADC value with no restricted diffusion was considered benign. DWI images findings had the 77% sensitivity and 75% specificity. Cho/Cr, Cho/ NAA ratios has highest sensitivity and specificity at short TE (96%,86%) Conclusion: DWI and MRS are helpful noninvasive techniques in detecting the malignant brain lesions and can help to avoid unnecessary biopsy in the patients suspecting brain lesions.